Utilization of Arbuscular Mycorrhizal Fungi and Bacillus velezensis Inoculation in Suppressing Twisted Disease of Shallot - Abdullah, Jilan Tsani; Suryanti, Suryanti; Joko, Tri (Jurnal Perlindungan Tanaman Indonesia, 2023)
Twisted disease is one of the problems in shallot cultivation. The application of the biological agents Bacillus velezensis and Arbuscular Mycorrhizal Fungi is an alternative expected to overcome disease problems in shallot plantings. The purpose of this study was to determine the effect of the application of B. velezensis and Arbuscular Mycorrhizal Fungi on the growth and health of shallot. The research was conducted in Gotakan, Panjatan, Kulon Progo, and the Phytopathology Laboratory, Department of Plant Protection, Faculty of Agriculture, Universitas Gadjah Mada, Yogyakarta. Shallot treatments with the application of biological agents were carried out either individually by soaking the bulbs in B. velezensis suspension before planting, coating the bulbs using Arbuscular Mycorrhizal Fungus (Rhizophagus intraradices) with a carrier medium of kaolin flour before planting, and a combination of spraying the B. velezensis suspension on plants at two-week intervals during the growth period and coating the bulbs before planting with R. intraradices. The results of the study showed that the shallot-applied single application of B. velezensis reduced the intensity and incidence of twisted disease by 2.51% and 37.6%, respectively. The combination treatment of B. velezensis and R. intraradices was able to increase the resistance of bulbs to postharvest pathogen Fusarium solani infection, with infected bulbs and areas of 0.70% and 0.71%, respectively.